Cambodia : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Cambodia achieved macroeconomic stability underpinned by prudent fiscal and monetary policies. Executive Directors commended this development. They welcomed the National Strategic Development Plan for reducing poverty, enhancing physical infrastructure, and improving social services. They appreciated the public financial management reform program, and encouraged to hasten the program's implementation by introducing the new Chart of Accounts for the budget and by rationalizing government bank accounts. They stressed the need to improve governance to enhance the business environment and strengthen revenue collection.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet